Meningococcal carriage among a university student population – United States, 2015. Issue 1 (2nd January 2018) - Breakwell, Lucy; Whaley, Melissa; Khan, Unab I.; Bandy, Utpala; Alexander-Scott, Nicole; Dupont, Lynn; Vanner, Cindy; Chang, How-Yi; Vuong, Jeni T.; Martin, Stacey; MacNeil, Jessica R.; Wang, Xin; et al.
Highlights: The vast majority of meningococcal carriage in this population was due to nongroupable strains. Prior to widespread serogroup B vaccine use, serogroup B carriage prevalence was relatively low. In a population with high MenACWY vaccine coverage, carriage due to serogroups C, W, or Y was rare. Abstract: Objectives: Several outbreaks of serogroup B meningococcal disease have occurred among university students in recent years. In the setting of high coverage of the quadrivalent meningococcal conjugate vaccine and prior to widespread use of serogroup B meningococcal vaccines among adolescents, we conducted surveys to characterize the prevalence and molecular characteristics of meningococcal carriage among university students. Methods: Two cross-sectional oropharyngeal carriage surveys were conducted among undergraduates at a Rhode Island university. Isolates were characterized using slide agglutination, real-time polymerase chain reaction (rt-PCR), and whole genome sequencing. Adjusted prevalence ratios and 95% confidence intervals were calculated using Poisson regression to determine risk factors for carriage. Results: A total of 1837 oropharyngeal specimens were obtained from 1478 unique participants. Overall carriage prevalence was 12.7–14.6% during the two survey rounds, with 1.8–2.6% for capsular genotype B, 0.9–1.0% for capsular genotypes C, W, or Y, and 9.9–10.8% for nongroupable strains by rt-PCR. Meningococcal carriage was associated with being male, smoking, party or club attendance, recent antibiotic use (inverse correlation), and recent respiratory infections. Conclusions: In this university setting, the majority of meningococcal carriage was due to nongroupable strains, followed by serogroup B. Further evaluation is needed to understand the dynamics of serogroup B carriage and disease among university students.